Advances in pharmacological treatment of type 1 diabetes during pregnancy. (24th May 2019) - Patti, Angelo Maria; Giglio, Rosaria Vincenza; Pafili, Kalliopi; Rizzo, Manfredi; Papanas, Nikolaos
ABSTRACT: Introduction : In women with type 1 diabetes mellitus (T1DM), pregnancy is associated with a potential risk of maternal, foetal and neonatal outcomes. Stringent metabolic control is required to improve these outcomes. Areas covered : In this review, the authors summarise the current evidence from studies on the pharmacological therapy and on monitoring of T1DM during pregnancy. The authors also discuss the use of new technologies to improve therapeutic management and patient compliance. Expert opinion : Pre-conception counselling is essential in T1DM to minimise pregnancy risks. Pregnancy in T1DM is always considered a high-risk pregnancy. During pregnancy, the target haemoglobin A1C (HbA1c ) is near-normal at <6%, without excessive hypoglycaemia. Strict control of pre- and post-prandial glucose is also required. Human soluble insulin, neutral protamine Hagedorn and the quick-acting insulin analogues aspart and lispro are widely used. Insulin is administered either as a basal-bolus regimen or by continuous subcutaneous insulin infusion. Careful and strict glucose monitoring is also needed during labour and delivery, including caesarean section. Moreover, the control of retinopathy, hypertension, nephropathy, hyper- and hypothyroidism is required. Post-partum, insulin requirements decrease, and less stringent glycaemic control is pursued, to avoid hypoglycaemias. Finally, breastfeeding is recommended and should be encouraged.